Loop ileostomy versus transverse colostomy as a covering stoma after anterior resection for rectal cancer - Bendary, Saied Hosny; El sheikh, Abd Elfatah T.; Ramadan, Mahmoud Kamal (International Surgery Journal, 2019)
Background: Most colorectal cancer occurs due to lifestyle and increase age with only a minority of cases associated with underlying genetic disorders and environmental factors enables us to move in the direction of a complete assessment of disease risk. The objective of the present study was to compare between two different types of diverting stoma (loop ileostomy and transverse colostomy) as regard immediate and remote complications in patient with rectal cancer treated by restorative resection. Methods: A prospective randomized comparative clinical study was conducted on 50 patients who underwent anterior resection and low anterior resection for rectal cancer divided into two groups: Group I consisted of 25 patients who underwent by loop ileostomy. Group II consisted of 25 patients who underwent by loop transverse colostomy. All patients attended to surgical oncology unit of Sayed Galal hospital, Al Azhar University, Cairo, Egypt during the period from October 2018 to October 2019. Full history, routine, physical examination, routine and imaging investigations were done. Results: 80% and 84% of loop ileostomy and transverse colostomy patients had anterior resection, respectively with no statistically significant differences between the two studied groups regarding anterior resection. Patient who treated by loop ileostomy had deceased time of closure (5.2±0.25 weeks) and stay in hospital (5.16±1.65 and 3.29±0.55 days) than those treated by transverse colostomy (9.6±0.37 weeks) and (7.44±2.58 and 6.03±1.97 days) respectively. Conclusions: Egyptians have unique tumor characters and behavior, and different compliance with treatment regimens. Multicenter prospective studies, as well as evolving Egyptian treatment guidelines are needed to address this.